Three dimensional intravascular ultrasonic assessment of the local mechanism of restenosis after balloon angioplasty. Issue 1 (1st January 2001) - Costa, M A; Kozuma, K; Gaster, A L; van der Giessen, W J; Sabaté, M; Foley, D P; Kay, I P; Ligthart, J M R; Thayssen, P; van den Brand, M J; de Feyter, P J; Serruys, P W
Abstract : OBJECTIVE: To assess the mechanism of restenosis after balloon angioplasty. DESIGN: Prospective study. PATIENTS: 13 patients treated with balloon angioplasty. INTERVENTIONS: 111 coronary subsegments (2 mm each) were analysed after balloon angioplasty and at a six month follow up using three dimensional intravascular ultrasound (IVUS). MAIN OUTCOME MEASURES: Qualitative and quantitative IVUS analysis. Total vessel (external elastic membrane), plaque, and lumen volume were measured in each 2 mm subsegment. Delta values were calculated (follow up − postprocedure). Remodelling was defined as any (positive or negative) change in total vessel volume. RESULTS: Positive remodelling was observed in 52 subsegments while negative remodelling occurred in 44. Remodelling, plaque type, and dissection were heterogeneously distributed along the coronary segments. Plaque composition was not associated with changes in IVUS indices, whereas dissected subsegments had a greater increase in total vessel volume than those without dissection (1.7 mm 3 v −0.33 mm 3, p = 0.04). Change in total vessel volume was correlated with changes in lumen (p < 0.05, r  = 0.56) and plaque volumes (p < 0.05, r  = 0.64). The site with maximum lumen loss was not the same site as the minimum lumen area at follow up in the majority (n = 10) of the vessels. In the multivariate model, residual plaque burden had an influence on negative remodelling (p = 0.001, 95% confidence interval (CI) −0.391 to −0.108), whereas dissection had an effect on total vessel increase (p = 0.002, 95% CI 1.168 to 4.969). CONCLUSIONS: The mechanism of lumen renarrowing after balloon angioplasty appears to be determined by unfavourable remodelling. However, different patterns of remodelling may occur in individual injured coronary segments, which highlights the complexity and influence of local factors in the restenotic process.